Reaction Time of Healthy Older Adults Is Reduced While Walking Fast. Issue 6 (2nd November 2019) - Richer, Natalie; Polskaia, Nadia; Raymond, Benjamin; Desjardins, Brigit; Lajoie, Yves
Abstract: Attentional requirements of walking at various speeds in older adults were examined. Twenty healthy older adults (69.9 ± 2.77 years; 8 males) were asked to walk a distance of 10 m at a self-selected speed as well as 30% quicker and 30% slower. Concurrently, reaction time (RT) was evaluated by having participants respond as fast as possible to randomly presented auditory stimuli. Results reveal that an accelerated walking speed generated faster RT than slow and self-selected speeds, while no difference was found between the latter. Faster RTs during an accelerated walking speed may have been precipitated by the reduced equilibrium demands of the task.